2018
DOI: 10.1021/acsami.8b16343
|View full text |Cite
|
Sign up to set email alerts
|

TC4/Ag Metal Matrix Nanocomposites Modified by Friction Stir Processing: Surface Characterization, Antibacterial Property, and Cytotoxicity in Vitro

Abstract: Numerous antibacterial biomaterials have been developed, but a majority of them suffer from poor biocompatibility. With the purpose of reducing biomaterial-related infection and cytotoxicity, friction stir processing (FSP) was employed to embed silver nanoparticles (Ag NPs) in a Ti–6Al–4V (TC4) substrate. Characterization using scanning electron microscopy, transmission electron microscopy, and three-dimensional atom probe tomography illustrates that NPs are distributed more homogeneously on the surface of TC4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…Copyright 2019, Elsevier) and b) typical Staphylococcus aureus ( S.a ) and Escherichia coli ( E.c ) colonies incubated on the samples after 24 h. The depth specifies the amout of Ag nanoparticles. (Reproduced with permission . Copyright 2018, ACS Publications).…”
Section: Advanced Surface‐modification Methodsmentioning
confidence: 99%
“…Copyright 2019, Elsevier) and b) typical Staphylococcus aureus ( S.a ) and Escherichia coli ( E.c ) colonies incubated on the samples after 24 h. The depth specifies the amout of Ag nanoparticles. (Reproduced with permission . Copyright 2018, ACS Publications).…”
Section: Advanced Surface‐modification Methodsmentioning
confidence: 99%
“…Here, silver nanoparticles placed in the preformed grooves on the surface of TC4 when subjected to FSP, they get homogenously distributed in the surface of TC4 matrix. The distribution profile of AgNPs is dependent on the depth of the preformed grooves [129,130]. On examination, it was observed that silver-rich NPs with a size ranging from 10 to 20 nm were diffused into the substrate.…”
Section: Surface Coating Using Ag-based Nanocompositesmentioning
confidence: 99%
“…TC4/Ag metal matrix nanocomposite is a potential nanocomposite that embeds AgNPs on a biomaterial surface for creating balance between the antibacterial effect and biocompatibility. The modified surface possesses an antibacterial properties [129,130].…”
Section: Surface Coating Using Ag-based Nanocompositesmentioning
confidence: 99%
“…Then, TiO 2 /TC4 composite coating, which provides a no biotoxicity environment for cells and promotes cell adhesion and proliferation, was produced [121]. Wang et al [122] produced a promising biomaterial−TC4/Ag metal matrix nanocomposite, which can achieve a balance between the antibacterial effect and biocompatibility. In Figure 20, with the increase of silver content, the number of staphylococcus aureus (S. aureus) cells decreased significantly and dead cells with an indistinct or deformed membrane were observed on 2 mm-Ag-FSP.…”
Section: Friction Stir Processingmentioning
confidence: 99%
“…In Figure 20, with the increase of silver content, the number of staphylococcus aureus (S. aureus) cells decreased significantly and dead cells with an indistinct or deformed membrane were observed on 2 mm-Ag-FSP. [122]. Reprinted with permission from reference [122] 2018 Elsevier.…”
Section: Friction Stir Processingmentioning
confidence: 99%